Design and characterization of a multi-layered polymeric drug delivery vehicle - Tan, K.; Ujan, S.; Danquah, M.; Lau, John (Wiley-Blackwell Publishing, 2019)
Aptamer-mediated targeted delivery is a promising advanced therapeutic delivery strategy with the potential to provide site-directed cyto-toxicity to malignant cells. However, effective translation of preclinical aptamer-navigated targeted delivery data into clinical success has been challenged by several biophysical and biochemical factors including rapid renal clearance, endonuclease-induced degradation, and cell membrane electrostatic repulsion. Aptamer-conjugated biopolymer systems represent new and smart drug carriers capable of delivering adequate amounts of drug molecules sufficient to elicit effective in vivo therapies at target sites in a controlled and sustained drug release pattern. In this work, a novel co-polymeric multi-layer BSA-loaded thrombin aptamer-conjugated PLGA-PEI (DPAP) formulation was synthesized using a w/o/w double emulsion and characterized layer-by-layer in vivo. DLS analysis of the DPAP particles showed a positively charged DPAP particulate system with a D[4,3] average hydrodynamic size of ~0.866 µm and a zeta potential of +9.85 mV. The zeta potential and D[4,3] average hydrodynamic size of DPAP layered compartments demonstrated pH-dependence but are not temperature dependent. The ionic strength of the binding medium affected the degradation and release rates of DPAP micro-particles. A strong binding strength and shielding effect of DPAP towards encapsulated BSA molecules was observed under increasing ionic strength. Thermogravimetric analysis showed that the DPAP formulation decomposes at ~300 °C, demonstrating the thermal stability of the polymer composite for effective storage in temperate environments. The data from this study is vital to engineer the interactions between DPAP polymeric system and cellular structures in order to enhance targeting events. While the DPAP construct demonstrates a great potential for targeted delivery, more in vivo delivery work is essential to prove its pre-clinical targeting capability.